PERAN SEMANTIS FRASA NOMINA YANG BERFUNGSI SEBAGAI ADVERBIAL DALAM KLAUSA BAHASA INGGRIS - Lily Marliah (Jurnal Sosioteknologi, 2009)
The purpose of the research : (i) to describe the construction of the noun phrase (NP) functioning as the adverbial in the English clause; (ii) ) to describe the semantic role of the noun phrase functioning as the adverbial (iii) to describe the verbs preceding the noun phrase functioning as the adverbial; (iv) to describe the prepositions preceding the noun phrase functioning as the adverbial when the noun phrase functions as the post-modifier of prepositional phrase. The technique used in the research is descriptive method with distributional technique. The research results: (i) the structures of the noun phrase (NP) functioning as the adverbial in the English clause may be found in prepositional phrases (noun phrase as the post-modifier or noun phrase with prepositional construction 'KBpr' and in noun phrase without prepositional construction 'KTpr'; (ii) the noun phrase with prepositional construction'KBpr' may have the semantic role as instrument, goal, source, path, and location; while the noun phrase without prepositional construction 'KTpr' may have the semantic role as the space position, space direction, space distance, time position, time duration, and time frequency. (iii) Adverbial (NP) with preposisitional construction'KBpr' having semantic role as instrument is preceded by the verbs : cut, wash, go, open, read, break, crack; having semantic role as goal is preceded by the verbs : walk, and go; having semantic role as source is preceded by the verbs : walk, and buy. Adverbial (NP) with preposisitional construction'KBpr' having semantic role as path is preceded by the verbs : walk, row, and drive; having semantic role as location is preceded by the verbs : sit, be, and find. Adverb of location (NP) without preposisitional construction'KTpr' having semantic role as space position is preceded by the verb : live; having semantic role as space direction is preceded by the verb : go; and having semantic role as space distance is preceded by the verbs :climb, run, hurry, travel. Adverb of time (NP) having semantic role as time position is preceded by the verbs : be, go, begin, stay, work; having semantic role as time frequency is preceded by the verbs : write, visit, go; and having semantic role as time duration is preceded by the verbs : live, and see. (iv) Adverbial noun phrases with prepositional construction'KBpr' having semantic role as instrument is preceded by the prepositions : with, on, by, by using, by means of ; having semantic role as goal is preceded by the preposition : to ; having semantic role as source is preceded by the preposition : from. Adverbial noun phrases with prepositional construction 'KBpr' having semantic role as path are preceded by the prepositions : through, along, on, and having semantic role as location are preceded by the prepositions : in, at on. Key words: noun phrase, adverbial, semantic role, verb, preposition